Are immigrants healthier than native residents? - Shoshana Neuman (IZA World of Labor, 2014)
In common anti-immigrant rhetoric, concerns are raised that immigrants bring diseases with them to the host country that threaten the health of the resident population. In reality, extensive empirical research over several decades and across multiple regions and host countries has documented that when immigrants arrive in the host country they are healthier than native residents, a phenomenon termed the "healthy immigrant effect." This initial advantage deteriorates with time spent in the host country, however, and immigrants' health status converges toward (or below) that of native residents.
Keywords: C25; D13; I12; J13; J71; Z12; 330; immigrants; natives; health; healthy immigrant effect; selectivity; acculturation; self-assessed health status